STUDENTS’ PERCEPTION ON THE DEVELOPMENT OF HALAL FOOD - Budi Eko Soetjipto, Puji Handayati, Rosmiza Bidin, Freddy Dwi Prasetyo (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Research on the development of halal food has not been done much in Indonesia. This study investigates the perceptions of master students of the management program concerning efforts to develop halal industries in East Java. in terms of 1) the role of government in halal certification, 2) halal food festival, and 3) promoting halal food events through social media and the internet. This study contended the value of halal recognition, halal certification, halal tourism events, and effective promotion strategies.